2014
DOI: 10.1039/c4sm01138d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic properties of interpolymer complexes assessed by isothermal titration calorimetry and surface plasmon resonance

Abstract: Interpolymer complexes (IPCs) formed between complimentary polymers in solution have shown a wide range of applications from drug delivery to biosensors. This work describes the combined use of isothermal titration calorimetry and surface plasmon resonance to investigate the thermodynamic and kinetic processes during hydrogen-bonded interpolymer complexation. Varied polymers that are commonly used in layer-by-layer coatings and pharmaceutical preparations were selected to span a range of chemical functionaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
4
22
1
1
Order By: Relevance
“…ITC is a very powerful method to study bimolecular interactions. It has been widely used to study interactions of polymers/biopolymers with other polymers, surfactants, small molecules, etc . It measures molecular interactions in solution in terms of changes in heat, which can be exothermic or endothermic depending on the nature of the interacting species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ITC is a very powerful method to study bimolecular interactions. It has been widely used to study interactions of polymers/biopolymers with other polymers, surfactants, small molecules, etc . It measures molecular interactions in solution in terms of changes in heat, which can be exothermic or endothermic depending on the nature of the interacting species.…”
Section: Resultsmentioning
confidence: 99%
“…ITC raw data showed the evidence of exothermic interaction between PAA and mucin (Figure S2). Exothermic effects are often associated with hydrogen bonding, which indicates that this could be a predominant nature of mucin–PAA interactions. This conclusion is in good agreement with Patel et al Sonication was found to have a significant ( p < 0.05) effect on the intensity of PAA–mucin interactions; stronger exothermic events are observed for sonicated mucin samples with higher Δ H values (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed mechanism of interactions between polymers is out of scope of the current study. Previously, the formation of IPC between PVA and negatively charged polymers such as polysaccharide, polyaspartic acids, and polyacrylic acid were reported [54][55][56]. Formed IPC associated with PVA-Hep led to a hindrance of sulfo groups of Hep with CHI, slowing down the formation of PEC at the studied temperature and concentration.…”
Section: Discussionmentioning
confidence: 94%
“…22,25,26 Biacore configuration and SPR chip construction Biacore 3000 from GE Healthcare is a real-time system for biomolecular interaction analysis using SPR technique. [27][28][29] With this method it is possible to monitor the formation and dissociation of biomolecular complexes on chip surfaces. CM5 (carboxymethyl dextran matrix) is served as a biochip for this research.…”
Section: Introductionmentioning
confidence: 99%